Deskriptif Penggembalaan Yang Sehat Menurut Kitab Titus Terhadap Pertumbuhan Jemaat GPSI Wilayah I - Riana Udurman Sihombing; Rahel Rati Sarungallo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2019)
The growth of a church is not instant. Expected growth cannot be separated from the influence of comprehensive teaching from a pastor and other instructors, the true growth process of the Church is inseparable from a way that is through discipleship, so that the congregation that he pastors may grow in quality and quantity to lead to the expected maturity by Christ.In fact in the church where the researchers joined, namely GPSI Shekinah Samarinda, the Assumption found several problems regarding the commitment of the congregation in GPSI Region I Samarinda. A temporary assumption is that not a few local church congregations do not reside or in other words like to move around church denominations.This is a sign that there is a problem with the so-called effect of a healthy shepherding on the growth of local congregations. This temporary assumption needs to be explored more depth in what causes and how local church congregations who are supposed to comply with local church rules, in fact do not implement and have no commitment to the local church.